2022
DOI: 10.1001/jamadermatol.2022.1964
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Patients With Lichen Sclerosus

Abstract: This case-control study uses data from the National Institutes of Health All of Us Research Program to investigate whether depression and anxiety are associated with lichen sclerosus among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Patients often experience anxiety, depression, and stress associated with their disease, which can adversely affect their quality of life and treatment outcome. VLS has been shown to have a signi cant impact on the mental and psychosocial health of women [20,21]. In our study, 61.2% of the patients considered it di cult to manage their fear of cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Patients often experience anxiety, depression, and stress associated with their disease, which can adversely affect their quality of life and treatment outcome. VLS has been shown to have a signi cant impact on the mental and psychosocial health of women [20,21]. In our study, 61.2% of the patients considered it di cult to manage their fear of cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Women with LS had a 2.16-to-2.5-fold increase or receiving a diagnosis of comorbid depression or anxiety compared with the control group. 32 However, Fiocco et al reported that no significant differences in stress levels were observed between both sexes. 13 Based on the Depression, Anxiety, and Stress Score (DASS-21), most patients experienced moderate to extremely severe depression, anxiety, and stress.…”
Section: Discussionmentioning
confidence: 97%
“…Patients often experience anxiety, depression, and stress associated with their disease, which can adversely affect their quality of life and treatment outcome. VLS has been shown to have a significant impact on the mental and psychosocial health of women [ 21 , 22 ]. In our study, 61.2% of patients considered it difficult to manage their fear of cancer.…”
Section: Discussionmentioning
confidence: 99%